Keragaman Genetik Aksesi Tanaman Kunyit (Curcuma longa L.) Berdasarkan Penanda Molekuler Simple Sequence Repeat (SSR) - Muthia Hanin Afidani; Noor Farid; Eka Oktaviani (Universitas Gadjah Mada, 2025)
A plant breeding program for turmeric (Curcuma longa L.) development is required to fulfil the pharmaceutical industry's demand. Understanding genetic diversity is the initial step in selecting the parents in plant breeding. Selection assisted by molecular markers, specifically Simple Sequence Repeat (SSR), can be used to obtain genetic information. However, genetic information on turmeric based on SSR markers in Indonesia is still limited. This study aimed to determine the genetic diversity and relationship of six accessions of turmeric using 4 (four) SSR primers. This study was conducted from October 2023 to January 2024 at the Laboratory of Plant Breeding and Biotechnology, Faculty of Agriculture, Universitas Jenderal Soedirman. The result showed that the CuMiSat-19, CuMiSat-20, and CuMiSat-29 primers were informative based on the electrophoresis band polymorphism. The CuMiSat-19 primer generated the highest PIC value (0,88), followed by CuMiSat-20 (0,80) and CuMiSat-29 (0,74). While CuMiSat-23 did not produce polymorphism, the PIC value was 0. The dendrogram classified six turmeric accessions into the two clusters with a Jaccard correlation coefficient range of 0.11-0.33. Cluster I consisted of accession A (Ponorogo), accession C (Gresik), accession D (Indramayu), and accession B (Semarang). Cluster II grouped accession E (Banyumas) and accession F (Bogor). Based on the polymorphism and similarity coefficient, turmeric accessions have a wide range of genetic diversity. Turmeric in different clusters is a potential germplasm that can be utilized to broaden genetic diversity in plant breeding programs.